User Interface Design for Citizen Data Grouping Information System Using Human Centered Design Method - Putra, Randi Rian; Putra, Eka; Handayani, Sri (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
User Interface is the initial display seen by the user on a system, this research was conducted in the village of klambir lima kebun. Klambir lima village is one of the villages in the hamparan perak sub-district with an area of 22.38 Km2, Klambir lima kebun village is bordered by, to the north bordering klumpang kebun village, to the south bordering tanjung gusta, to the east bordering Helvetia, to the west bordering klambir lima kampung. The Information System for grouping data on residents of the village of Klambir Lima Kebun is a system that is built based on user interface design with a responsive mobile system that is tested based on usability with the uman centered design method. Uman centered design is a method of approach in developing and designing a system that focuses on users according to aspects of the needs and habits of users. In the village of Klambir Lima Kebun, information about the population has not been done optimally and does not have a program to support work in the office. Office employees have difficulty in categorizing population data, still using manual methods or still in paper form. With this system design, it can help village officials in the process of grouping citizen data and accelerating services to the community and providing more effective and accurate information.